__Enter two polynomials to perform operations on:__

__Using polynomial long division, evaluate the expression below:____First, we write our expression in long division format and follow the steps below.__

**Step 1** 1a) Divide the first term of the

**dividend** by the first term of the

**divisor** →

**x**^{2} ÷

**x** = 1x

^{(2 - 1)} =

**x** 1b) We multiply that part of the

**quotient** by the

**divisor** →

**x**(

**x - 3**) =

**x**^{2} - 3x →

Click here to see the Math for this Multiplication. 1c) Subtract

**x**^{2} - 3x from

**x**^{2} - 6x + 8 to get

**-3x + 8** →

Click here to see the Math. | | | x |

x | - | 3 | x^{2} | - | 6x | + | 8 |

| | | x^{2} | - | 3x | | | | | |

| | | | | -3x | + | 8 | | | |

**Step 2** 2a) Divide the first term of the

**dividend** by the first term of the

**divisor** →

**-3x** ÷

**x** = -3x

^{(1 - 1)} =

**-3** 2b) We multiply that part of the

**quotient** by the

**divisor** →

**-3**(

**x - 3**) =

**-3x + 9** →

Click here to see the Math for this Multiplication. 2c) Subtract

**-3x + 9** from

**-3x + 8** to get

**-1** →

Click here to see the Math. | | | x | - | 3 |

x | - | 3 | x^{2} | - | 6x | + | 8 |

| | | x^{2} | - | 3x | | | | | |

| | | | | -3x | + | 8 | | | |

| | | | | -3x | + | 9 | | | |

| | | | | | | -1 | | | |

We have a remainder leftover. We take our answer piece and remainder piece below

Answer =

**x - 3**Remainder piece = Leftover answer divided by our denominator

[+] __Watch the Algebra Master (Polynomials) Video__